Pengembangan Produk Bakso yang Berbahan Baku Berantioksidan - Wellyalina Wellyalina; Daimon Syukri (REACTOR: Journal of Research on Chemistry and Engineering, 2020)
The development of functional food is increasing. Meatball is a popular food product that can be developed to be more functional by adding antioxidants. Meatballs are processed products from small round meat. This study aims to obtain the best formula for meatball production with high antioxidant content and good organoleptic characteristics. The addition of Moringa leaves, celery, panax cup leaves, and lime leaves to the original meatball production formula was used as a treatment in this study. The research method uses an exploratory method through laboratory experiments. The treatment used was the addition of Moringa leaves, celery, bowl, and lime leaves. Each treatment was added with a different main ingredient as much as 3.3% with 3 repetitions so that the results can be said to be valid. The results showed that the addition of panax cup leaves could produce functional meatballs with the best antioxidant and organoleptic properties among all treatments.